Filtrodynamics 2: Effects of Particle Size and Filter Type on Trans‐Filter Time‐Dependent Pressure Signals. Issue 7 (22nd January 2014) - Dufrechou, Marie; Mignard, Emmanuel; Drenski, Michael F.; Reed, Wayne F.
Abstract Filtrodynamic behavior of trans‐filter time‐dependent pressure signals ΔP(t) is determined for membrane and frit filters using latex spheres of varying diameter D. Membrane data are best interpreted via a time‐dependent, accreting filtration bed, based on Darcy's law. A single parameter, permeability k, describes each membrane/particle pair. For small particles, k increases with increasing D, then becomes D‐independent for large ones. Predictable behavior for polydisperse mixtures of small spheres is obtained. The mechanism and behavior of filtration for non‐membrane metallic frits is dramatically different, and better described by a previous "characteristic loading" model. Use of frit and membrane filters in series allowed monitoring each filter's separate response to particle accumulation.<inline-graphic xlink:href="ark:/27927/pghqb9ppz5" content-type="mren201300185-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />